Wild passerines as potential carriers and sources of avian influenza viruses in Ukraine - Muzyka, Nataliia; Popova, Anastasia; Rula, Oleksandr; Yurko, Polina; Chaplygina, Anzhela; Byrne, Alexander M. P.; Lofts, Abi; Zohari, Siamak; Koethe, Susanne; Fair, Jeanne; Owen, Jen; Lewis, Nicola; et al. (Frontiers in Microbiology, 2026)
Wild waterfowl and shorebirds are the primary reservoir of influenza A viruses in nature. The role of wild birds from other taxonomic groups remains insufficiently studied or is a subject of debate. This applies in particular to Passeriformes, the most diverse avian order, accounting for approximately 60% of the global bird population, where the role in circulation of influenza A viruses is underexplored. We used serological, virological, and PCR-based methods to survey avian influenza viruses in Passeriformes birds (65 species, 20 families) in Ukraine over a 20-year period, 2004–2025. Antibodies to influenza viruses were detected in serum and egg yolk of seven passerine species, with average seroprevalence 1.24% in sera and 8.94% in yolk samples. Seroprevalence varied across species, ranging from 1.96 to 27.2%. Virological screening resulted in the isolation of two viruses from Fieldfares (Turdus pilaris) of the subtypes H1N1 and H7N1. The overall infection rate based on virus isolation was 0.15%, while local infection rate in Fieldfares reached 11.1%. According to PCR results, 41 positive samples were detected, representing 3.61% of all tested birds (ranging from 1.42–9.1%), and by location ranged from 6.25–9.1%. Sequencing and phylogenetic analyses of H1N1 (Fieldfare), H7N1 (Fieldfare), H3N8 (Great Tit Parus major) influenza viruses confirmed them as Eurasian lineage low pathogenic avian influenza viruses and with close relatedness to viruses of the same subtypes circulating among wild waterfowl.